Answer:
x = 7
Step-by-step explanation:
Let
x = the unknown number
double it :
2x
add 11:
2x + 11
I get 25:
The equation is
2x + 11 = 25
2x = 25 - 12
2x = 14
Divide both sides by 2
x = 14/2
x = 7
The given conditional statement is : If 7<5, then 5<3.
Inverse: If 7≥5 then 5≥3 (The inverse is true)
Contrapositive: if 5≥3 then 7≥5 (The contrapositive is true)
Converse: if 5<3 then 7<5 (The converse is true)
From the properties of conditional statement we know that:
if p→q then
- inverse is :
![\backsim p \rightarrow \backsim q](https://tex.z-dn.net/?f=%5Cbacksim%20p%20%5Crightarrow%20%5Cbacksim%20q)
- contrapositive:
![\backsim q \rightarrow \backsim p](https://tex.z-dn.net/?f=%5Cbacksim%20q%20%5Crightarrow%20%5Cbacksim%20p)
- Converse:
![q \rightarrow p](https://tex.z-dn.net/?f=q%20%5Crightarrow%20p)
Let us elaborate on the above conditions. Let us take two statement p and q such that If p happens then q also happens.
- The inverse of a conditional statement is given as "if not p then not q"the converse is given as "if q then p"The contrapositive of the statement states "if not q then not p"
- The following statements can be used for converting the conditional statements to its inverse, converse or contrapositive.
To learn more about conditional statements:
brainly.com/question/7066208
#SPJ4
Answer: 175, 210, 245
Step-by-step explanation:
Answer: Infinite solutions.
Step-by-step explanation:
![y=-2x-6\\2y=-4x-12](https://tex.z-dn.net/?f=y%3D-2x-6%5C%5C2y%3D-4x-12)
Plug the value of y into the second equation.
![\\ 2(-2x-6)=-4x-12\\-4x-12=-4x-12](https://tex.z-dn.net/?f=%5C%5C%202%28-2x-6%29%3D-4x-12%5C%5C-4x-12%3D-4x-12)
Add 12 on both sides.
![-4x-12+12=-4x-12+12\\-4x=-4x](https://tex.z-dn.net/?f=-4x-12%2B12%3D-4x-12%2B12%5C%5C-4x%3D-4x)
Add 4x on both sides.
![-4x+4x=-4x+4x](https://tex.z-dn.net/?f=-4x%2B4x%3D-4x%2B4x)
![0=0](https://tex.z-dn.net/?f=0%3D0)
The answer would be 54. Because you start with 2.
2x3 = 6
6x3 = 18
18x3 = 54
Each month it triples so you continue
to add 3 to each result.